Decrease of MiR‐31 induced by TNF‐α inhibitor activates SATB2/RUNX2 pathway and promotes osteogenic differentiation in ethanol‐induced osteonecrosis. Issue 4 (21st August 2018) - Yu, Lingjia; Xu, Yisheng; Qu, Hao; Yu, Yifeng; Li, Wenjing; Zhao, Yu; Qiu, Guixing
Abstract : Purpose: Suppressed osteogenic differentiation is considered a main cause of ethanol‐induced osteonecrosis. Tumor necrosis factor α (TNF‐α) and miR‐31 have been reported to be involved in the osteogenic induction. This study aimed to explore a possible molecular mechanism regulating osteogenic differentiation in ethanol‐induced osteonecrosis bone marrow stromal stem cells (BMSCs). Methods: Alizarin red staining was used to examine the level of mineralization in osteogenic differentiation process. Alkaline phosphatase assay was applied to the validation of ALP level which was essential to bone mineralization. The level of osteogenesis markers was determined by western blot assay, whereas the fluctuations of messenger RNA levels were tested by quantitative real‐time polymerase chain reaction. Microarray analysis was conducted to identify differentially expressed genes, because the possible target relationship was predicted and validated by miRBase and luciferase reporter assay, respectively. Colony forming unit of fibroblast assay was used to observe the proliferation of BMSCs. Results: BMSCs from patients with ethanol‐induced osteonecrosis exhibited weaker osteogenic differentiation and proliferation abilities. TNF‐α inhibitor added in the osteogenic medium significantly enhanced the osteogenic differentiation ability and BMSCs proliferation ability. TNF‐α by regulating miR‐31 downregulated the expressions of RUNX2 and SATB2, two contributors of osteoblast differentiation, further suppressed osteogenic differentiation. On the contrary, TNF‐α inhibitor could promote osteogenic differentiation in BMSCs from patients with ethanol‐induced osteonecrosis. Conclusion: TNF‐α inhibitor could downregulate miR‐31 expressions, which directly promoted SATB2 and RUNX2 expressions and enhanced osteogenic differentiation of BMSCs from patients with ethanol‐induced osteonecrosis. Abstract : Tumor necrosis factor α (TNF‐α) inhibitor could influence the expression of miRNA and regulate the process of osteogenic differentiation. MiR‐31 was identified to be highly expressed in osteonecrosis tissues and negative‐regulated SATB2/RUNX2 pathway. TNF‐α inhibitor might provide potential therapies for patients with ethanol‐induced osteonecrosis in the future.